Sistema de clases para mejorar el speaking a través del enfoque comunicativo - Aguilar Davila, Vicente Joel; Molina Orozco, Nathaly Kaenia (Machala, Utmachala, 2022)
The purpose of this research work is to improve the speaking level of English students through a classroom system, which is oriented towards the development of communication strategies, the creation of meaningful learning and the strengthening of the teacher-student bond. This research is defined by the qualitative paradigm, employing theoretical methods such as the historical-logical, Inductive-Deductive. As well as empirical methods such as Systemic Observation and Pedagogical Test. Also, it focuses on the communicative approach, which, through emphasis on interaction, develops communicative competence and introduces real situations to the learning field that contribute to improve students' confidence and effectiveness in the English language. Therefore, the proposal is defined and the classroom system is applied to test the effectiveness of the communicative approach to improve the speaking level of English language learners.
Este trabajo de investigación tiene como objetivo mejorar el nivel de speaking en los estudiantes de inglés a través de un sistema de clases, el cual está orientado en el desarrollo de estrategias de comunicación, creación de aprendizaje significativo y fortalecimiento del vínculo entre docente-estudiante. Esta investigación se defiende en el paradigma cualitativo, empleando métodos teóricos como el histórico-lógico, Inductivo-Deductivo. Así como métodos empíricos tales como la Observación Sistémica y la Prueba Pedagógica. También su estudio se centra en el enfoque comunicativo, el cual, mediante énfasis en la interacción, desarrolla la competencia comunicativa e introduce situaciones reales al campo de aprendizaje que contribuyen a mejorar la confianza y efectividad de los estudiantes en el idioma inglés. Por lo tanto, se define la propuesta y se aplica el sistema de clases para comprobar la efectividad del enfoque comunicativo para mejorar el nivel de speaking en los estudiantes de inglés.
Keywords: ENFOQUE COMUNICATIVO; SPEAKING; ESTRATEGIA DE COMUNICACION; INTERACCION; COMPETENCIA